KEMISKINAN DAN KETIMPANGAN PENDAPATAN RUMAH TANGGA DI KABUPATEN BOJONEGORO - Sugiyarto Sugiyarto; Jangkung Handoyo Mulyo; Rosalia Natalia Seleky (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
Poverty and inequality have become challenges for most developing countries in the world. Large number of the poor are concentrated in the rural area, and mostly are farmer. The objectives of the study were to identify the poverty occurrence in the rural Bojonegoro and, to analyze the income inequality among them. This research was conducted in rural areas in Bojonegoro Regency, and there were 60 rural households interviewed. The FGT index (Headcount index, Poverty Gap index and Poverty Severity index) and the Criterions of BPS, World Bank, and Asian Development Bank were introduced to identify the poverty occurred in the rural area. Meanwhile, the Gini index and Lorentz curve were employed to measure the income inequality among those households. The result shows that the level of poverty in rural Bojonegoro considered to be quite high (based on the criterions of World Bank and Asian Development Bank), on the contrary, based on BPS criteria, the poverty level is fairly low. The ‘depth of poverty’ score measured by the FGT index is 0.05, meanwhile the ‘severity of poverty’ score is 0.02. Furthermore, the income is distributed unequally among the rural households showed by the Gini index of 0.459.